Land-use change and solar energy production: A real option approach - Ardjan Gazheli; Luca Di Corato (Fondazione Eni Enrico Mattei (FEEM), 2011)
In this paper a real option model is developed to examine the critical factors affecting the decision to lease agricultural land to a company installing a PV power plant. The leasing payment is certain while the net revenues from agriculture are uncertain. We identify the profit values at which the farmer decides to lease his plot vs. continue farming it. By applying the model to the province of Bologna (Italy), we illustrate the possible land-use change scenarios in this area. We conclude by discussing the importance of PV energy production as a source of income for farmers and its implications from a social perspective.
Keywords: C61; D81; Q24; Q42; 330; Land Allocation; Real Options; Renewable Energy; Solar farm; Uncertainty